Contagious molluscum in swimmers with atopic dermatitis: transmission risk, clinical challenges and impact on sports participation - a narrative review - Zinko, Oksana; Zimnoch-Włodarczyk, Aleksandra; Łapiński, Maciej; Napierała, Michał; Ciecierska, Kinga; Wasilkowska, Krystyna; Łatkowska, Sylwia; Więcek, Laura; Ściurka, Kinga (Journal of Education, Health and Sport, 2026)
Background. Molluscum contagiosum (MC) is a common cutaneous poxvirus infection transmitted primarily through direct skin-to-skin contact and autoinoculation, with indirect spread via fomites considered plausible in shared environments. Swimmers may face heightened exposure to communal facilities and equipment, while atopic dermatitis (AD) can amplify susceptibility and disease burden through skin-barrier dysfunction and itch-driven dissemination. These factors can create clinical uncertainty about transmission risk, complicate management, and contribute to unnecessary restriction from training and competition. Material and methods. A narrative review was conducted using targeted searches of PubMed/MEDLINE and Google Scholar, supplemented by screening of reference lists and verification through official journal/publisher records. Search terms combined MC with AD-related constructs (eczema, filaggrin/barrier dysfunction) and aquatic/sport contexts (swimming, pools, athletes, transmission, fomites, return-to-play), and were expanded to include contemporary therapeutics relevant to clearance timelines. Results. The evidence base supports contact and autoinoculation as the dominant transmission pathways for MC, while direct evidence for chlorinated pool water as a primary vehicle remains limited; the swimmer setting is more plausibly “facility-associated” through shared surfaces, changing areas, and personal items. AD consistently emerges as a risk amplifier and phenotype modifier, with barrier dysfunction and pruritus promoting wider lesion dissemination and eczematization that can obscure diagnosis and complicate treatment tolerability. Therapeutic advances supported by randomized trials, including provider-applied cantharidin 0.7% formulations and topical nitric oxide–releasing berdazimer gel, offer practical options to reduce lesion burden and support time-sensitive participation planning.